Enzymes and biopolymers. The opportunity for the smart design of molecular delivery systems. (February 2021) - Rivero Berti, Ignacio; Islan, German A.; Castro, Guillermo R.
Graphical abstract: Highlights: Biopolymers can be obtained from agricultural wastes with low cost. Enzymes can be produced by fermentation or recovery from wastes. Biopolymers can be used to develop matrices for molecular controlled release. Smart biopolymeric matrices can be activated in situ by enzymes. Biopolymer-enzymes systems can be able to increase molecular delivery efficiency. Abstract: Enzymes exhibit a tremendous potential due to the catalytic activity in response to physiological conditions and specific microenvironments. Exploiting these properties in combination with the versatility of biopolymers, a fascinating field for the rational development of a new class of "smart" delivery systems for therapeutic molecules is proposed. Many strategies have been recently developed to produce matrices with the desirable properties of molecular release, and enzymes could be playing a relevant role in modify the chemical composition of the polymers, the porosity and surface area of the matrices and modulate the kinetic of controlled release. Enzyme based computational systems have appeared as a relevant complementary tool to design novel smart bioactive matrices for programmable drug delivery. The present review is reporting the recent advances and projections of smart biopolymeric matrices activated by enzymes for sustained release of therapeutic molecules, highlighting various applications in the area of advanced drug delivery.